Inside Cover: Benzoxazolone Carboxamides: Potent and Systemically Active Inhibitors of Intracellular Acid Ceramidase (Angew. Chem. Int. Ed. 2/2015). Issue 2 (21st November 2014) - Pizzirani, Daniela; Bach, Anders; Realini, Natalia; Armirotti, Andrea; Mengatto, Luisa; Bauer, Inga; Girotto, Stefania; Pagliuca, Chiara; De Vivo, Marco; Summa, Maria; Ribeiro, Alison; Piomelli, Daniele
<x xml:space="preserve">Abstract</x> The discovery of the first potent systemically active inhibitors of acid ceramidase (AC) are reported in the Communication by D. Piomelli and co‐workers on page 485 ff. This enzyme controls the levels of two key intracellular messengers: ceramide, which causes cell senescence and death, and sphingosine‐1‐phosphate (S1P), which has the opposite effect. By blocking AC, the new inhibitors tilt the balance between ceramide and S1P, thereby enhancing the pro‐aging and pro‐death effects of the former compound.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>